2013
DOI: 10.1603/ec12472
|View full text |Cite
|
Sign up to set email alerts
|

Use of Black Light Traps to Monitor the Abundance, Spread, and Flight Behavior of <I>Halyomorpha halys</I> (Hemiptera: Pentatomidae)

Abstract: Monitoring the distribution and abundance of an invasive species is challenging, especially during the initial years of spread when population densities are low and basic biology and monitoring methods are being investigated. Brown marmorated stink bug (Halyomorpha halys (Stål)) is an invasive agricultural and urban pest that was first detected in the United States in the late 1990s. At the time of its detection, no method was available to effectively track H. halys populations, which are highly mobile and pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 18 publications
1
48
0
1
Order By: Relevance
“…Its population growth can also be due to successful establishment and spread in Trentino by benefiting from host availability and being released from natural enemy pressure, leading to increased population density and fitness [53]. Similar observations in New Jersey, USA, concluded that BMSB underwent a population increase of 75% each year, during the period spanning from 2004 to 2011 [54]. An alternative mechanism in invasion ecology that could be linked to BMSB success is the Evolution of Increased Competitive Ability (EICA).…”
Section: Invasion Dynamics In Trentinomentioning
confidence: 68%
“…Its population growth can also be due to successful establishment and spread in Trentino by benefiting from host availability and being released from natural enemy pressure, leading to increased population density and fitness [53]. Similar observations in New Jersey, USA, concluded that BMSB underwent a population increase of 75% each year, during the period spanning from 2004 to 2011 [54]. An alternative mechanism in invasion ecology that could be linked to BMSB success is the Evolution of Increased Competitive Ability (EICA).…”
Section: Invasion Dynamics In Trentinomentioning
confidence: 68%
“…In agricultural settings, UV light traps are commonly used to monitor population levels of pest species (Nielsen et al 2013). Even when pheromones or other species-specific methods for trapping an insect have been developed, it is helpful to identify the effect of light as an additional incorporation into trapping devices or protocols (Duehl et al 2011;Leskey et al 2015b).…”
mentioning
confidence: 99%
“…Population monitoring and both preemptive and responsive pesticide application are currently the primary strategies employed for control of this pest (Leskey et al 2012a(Leskey et al , 2012b. Furthermore, UV light traps have been successfully used to monitor for H. halys on both local and regional scales (Nielsen et al 2011;Nielsen et al 2013;Wallner et al 2014).…”
mentioning
confidence: 99%
“…The available evidence suggests that movement of N. viridula into cotton from other host plants can occur over small spatial scales (Olson et al 2012;Tillman 2014;Tillman et al 2014;Tillman et al 2009), something that is found in similar pentatomid pests that include Halyomorpha halys (Nielsen et al 2013;Venugopal et al 2014;Wallner et al 2014), Chinavia hilaris (Tillman et al 2015), as well as Euschistus conspersus and Thyanta pallidovirens (Pease & Zalom 2010). Long distance and interannual movement of pentatomids, including N. viridula, has been given less attention.…”
Section: Introductionmentioning
confidence: 99%
“…halys also changes at different times of the year and at different temperatures (Lee 2015), and monitoring of its spread in the USA (Nielsen et al 2013;Wallner et al 2014) suggests that, while longdistance dispersal in pentatomids does occur, it may happen gradually.…”
Section: Introductionmentioning
confidence: 99%